2016
DOI: 10.1128/jvi.02278-15
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Antibody Neutralization Breadth Is Associated with Enhanced HIV-Specific CD4 + T Cell Responses

Abstract: Antigen-specific CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…This unlinked recognition can result in germinal center formation, hypersomatic mutation, and the generation of strongly neutralizing antibodies (39). Evidence for this model has been shown previously in studies describing the correlation of strongly neutralizing antibodies against the HIV-1 envelope with CD4 T-cell recognition of Gag epitopes (40) and the enhancement of antihemagglutinin-specific antibody responses by the adoptive transfer of CD4 T cells that recognized influenza virus matrix and nucleocapsid proteins (39); also, the expres-…”
Section: Discussionmentioning
confidence: 94%
“…This unlinked recognition can result in germinal center formation, hypersomatic mutation, and the generation of strongly neutralizing antibodies (39). Evidence for this model has been shown previously in studies describing the correlation of strongly neutralizing antibodies against the HIV-1 envelope with CD4 T-cell recognition of Gag epitopes (40) and the enhancement of antihemagglutinin-specific antibody responses by the adoptive transfer of CD4 T cells that recognized influenza virus matrix and nucleocapsid proteins (39); also, the expres-…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we incorporated a promiscuous T-cell TT epitope to harness the MHC-II antigen presentation pathway that has been shown as a major limiting factor in MPER responses in murine models37. Likewise, in a cohort of untreated HIV-1 infected viremic controllers it has been recently shown an association between gp41-specific CD4 T cell responses with the magnitude and breadth of anti-Env neutralizing antibodies63. We incorporated gp41-MinTT protein into liposomes of diverse composition.…”
Section: Discussionmentioning
confidence: 99%
“…While elevated percentages of CD8 + CD57 + T cells have been described as a symptom of chronic immune activation [48] and of accelerated immune senescence in chronic HIV infection [49], several studies have also shown that CD8 + CD57 + T cells elicit potent cytotoxic effector functions in HIV and other viral infections [50,51] through high expression of perforin and secretion of IFN-γ and TNF-α [52]. A recent study comparing HIV-specific T cell responses in neutralizers and non-neutralizers showed a greater breadth and magnitude of CD4 + T cell responses to HIV Gag by ELISPOT in neutralizers versus non-neutralizers [37], suggesting a more effective CD4 T cell response. In addition, our data showing that CD8 + CD57 + T cell frequencies correlated positively with total CD8 + T cell frequency and negatively with CD4 + CD25 + T cell frequencies may indicate that elevated frequencies of CD8 + CD57 + T cells in VC with high neutralization breadth reflect reduced T regulatory and increased cytotoxic T cell frequencies in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this group was further subdivided according to the median, and subjects with breadth of 1 to 4 were classified as low-neutralizers ( n =18), and subjects with breadth ≥5 were classified as high neutralizers (neutralizers; n =14). Similar stratifications have been applied previously [3741]. Neutralization groups were matched for gender, age, ethnicity, time since HIV diagnosis and prior use of cART (Table 1).…”
Section: Methodsmentioning
confidence: 99%